Herd management and breeding practices of holla sheep owners in south wollo zone, Ethiopia - Akale, Adina; Mengesha, Tadlo; Getu, Addis; Abegaz, Solomon (International Journal of Biological Research, 2017)
This study was aimed to generate organized information on selective breeding objectives, trait's preferences and major constraints of the Holla sheep production system in Kalu and Worebabo districts of South Wollo Zone under small holders' management conditions. The study was performed based on the semi-structured questionnaire, focused group discussions. Secondary data source analysis and field observations were used to generate the required information. In addition, simple random sampling technique was used to select 180 sheep owners. Simple descriptive statistics, ranking trial and chip-square test was considered. The primary purpose of keeping sheep was asset development (income generation) followed by breeding purposes with the index value of 0.365 and 0.201, respectively. Body size/Appearance was the primary preference in both districts for breeding ram index value of 0.258 and 0.207 Kalu and Worebabu, respectively. In the study areas, culling inferior sheep, weaning, record keeping, castrating ram at right age and provision of regular vaccination before disease out breaks were poorly practiced. Age at first sexual maturity of male sheep was 7.3±2.17and 7.23±1.34 months while for females 7.9±1.87 and 5.8±1.16 months in Kalu and Worebabo district, respectively. Disease prevalence and genetic potential were the major production constraints in the entire studied districts. In order to minimize the failure of breed improvement programs it is important to involve farmers considering the existing breeding practices, management systems and trait preferences of the community and the multipurpose roles of targeted animals.